Istota funkcji informacyjnej rachunku kosztów w sektorze małych przedsiębiorstw - Zuchewicz, Joanna (The Concept of Costs Account Informative Function in the Sector of Small Enterprises, 2007)
Accountancy in small enterprises provides mainly the information indispensable for preparing financial, statistical and tax statements. However, the data referring to costs or possibly other figures included in the system of accountancy, may be imported from the financial-accounting programme to the system of costs account, in which they are grouped, depending on the needs in due cross-sections, in order to analyze them and supply crucial information for the process of small enterprise management. Generally speaking, having in mind the simplifications applied in the system of accountancy as well as the tax policy adopted by owners of small units the costs account is observed as the only, true source of information about the amount of costs incurred and results achieved, about a product or service unit cost as well as the profitability of conducted economic activities. It is only on the basis of the above data that small enterprises may carry out their objectives in a successful way.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 549-555